Autonomy Supportive Contexts, Autonomous Motivation, and Self-Efficacy Predict Academic Adjustment of First-Year University Students - Girelli, Laura; Alivernini, Fabio; Lucidi, Fabio; Cozzolino, Mauro; Savarese, Giulia; Sibilio, Maurizio; Salvatore, Sergio (Frontiers in Education, 2018)
Aim. The purpose of this study was to provide a better understanding of undergraduate students' academic adjustment in the first year of higher education, by testing a predictive model based on self-determination theory with the inclusion of self-efficacy. The model posits that perceived autonomous forms of support from parents and teachers foster autonomous motivation and self-efficacy, which in turn predict academic adjustment. Method. A two-wave prospective design was adopted. Freshman students at an Italian university (N = 388; 73.5% females, M age = 21.38 years ± 4.84) completed measures of autonomous motivation, perceived autonomy support from parents and teachers, self-efficacy, and intention to drop out from university at the start of their academic year. Students' past performance and socioeconomic background were also measured. At the end of the first semester, information about number of course modules passed and credits attained for each student were collected from the department office and matched with the data collected in the first wave by an identification number. Results. Findings of structural equation modeling analysis supported the proposed model for first-year university students, after controlling for the influence of past performance and socioeconomic background. Specifically, autonomous motivation and self-efficacy predicted dropout intention and academic adjustment a few months later. Autonomous motivation and self-efficacy were encouraged by autonomy supportive behaviors provided by teachers and parents. Conclusion. According to our findings, in order to promote higher degree of academic adjustment in freshman students, interventions should aim to encourage autonomous motivation and self-efficacy through autonomous supportive behavior from the university and the family contexts.